2006
DOI: 10.1080/10428190600687281
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recurrent Langerhans cell histiocytosis in children with 2-chlorodeoxyadenosine

Abstract: The objective of this study was to evaluate the efficacy of 2-chlorodeoxyadenosine (2-CdA), a purine nucleoside analog, in treating recurrent Langerhans cell histiocytosis (LCH) in children. This study retrospectively analysed the clinical records of 13 patients who were seen in the department for recurrent LCH. These patients were treated consecutively with 2-CdA chemotherapy between July 1997 and May 2005. Median age at diagnosis was 4 years 7 months and median pre-treatment duration of disease was 16.4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Several recent reports have shown that 2-chlorodeoxyadenosine (2-CdA), which is a purine substrate analog, is an effective treatment for refractory or reactivated childhood MS LCH [3,4]. In adult LCH patients, 2-CdA has been used as a first-line therapy [5], but its efficacy in childhood LCH is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports have shown that 2-chlorodeoxyadenosine (2-CdA), which is a purine substrate analog, is an effective treatment for refractory or reactivated childhood MS LCH [3,4]. In adult LCH patients, 2-CdA has been used as a first-line therapy [5], but its efficacy in childhood LCH is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, PNA administration has become a useful tool in treating young persons and even children. Indeed, positive effects of cladribine in the treatment of chronic lymphocytic leukemia have been described (Chow et al 2000), as its efficacy in treating NHL [Chow et al 2000], mantle cell lymphoma (Inwards et al 2008), AML (Wierzbowska et al 2008), myelodysplastic syndromes (Laurencet et al 1997), chronic myeloid leukemia (Martinelli et al 1996), Waldenström macroglobulinemia (Rourke et al 2010), histiocytosis, also in children (Mottl et al 2006), astrocytomas (Ceruti et al 2000, Ceruti et al 2003), multiple sclerosis (Hartung 2009; Leist and Weissert 2011; Vosoughi and Freedman 2010), mast cell disease (Aichberger et al 2008), psoriasis, including psoriatic arthritis (Eibschutz et al 1995), systemic lupus erythematosus (Bernknopf et al 2011), angioedema, and anaphylaxis (Dutta et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Isolated LCH as bone and genital lesions have a tendency to spontaneous regression, and radiotherapy should not be a front line treatment, mainly for adolescents (20,26) . Some experiences confirmed efficacy of 2-CdA in the treatment of LCH (27)(28)(29)30) . The primary systemic chemotherapy with VBL and PDN (LCH II-LR protocol) in our patient showed only an 8-month remission followed by a local recurrence.…”
Section: Discussionmentioning
confidence: 75%